Estudio Bibliométrico y Mapa de Redes del Tecnoestrés Docente. Entre 1992-2022 - Louzán Mariño, Rita; Torrano, Fermín (Comunicar, 2024)
The purpose of this research was to realize a metric study of scientific production between1992 and 2022 on one of the topics that has acquired great importance in the educational field, due to the pandemic caused by COVID-19: teacher technostress. For such purpose, 139 scientific documents indexed in the Web of Science database were examined. The content was analyzed using an Excel spreadsheet and the VOSviewer software. To guarantee the quality of the methodological procedure, the PRISMA protocol was followed. First, a bibliometric analysis of the extracted publications was conducted, taking several indicators of production and dispersion as references. Second, a network analysis was performed to understand the collaboration structure between countries and the conceptual structure of the topic under study. The results highlight that existing scientific information on teacher technostress is scarce, that it is widely dispersed in terms of research areas, and that there are no major producers on the subject. Nonetheless, COVID-19 has been a decisive turning point that has generated the highest percentage of scientific production recorded to date and has contributed to bringing greater visibility to technostress, not only as a psychosocial occupational risk but also as a phenomenon affecting the teaching profession as one of the most vulnerable work collectives in an online context.
Bibliometric Study and Network Mapping of Teacher Technostress Between 1992-2022
El propósito de esta investigación es realizar un estudio métrico de la producción científica generada en el periodo 1992-2022 sobre uno de los tópicos que ha adquirido mayor importancia en el ámbito educativo debido a la pandemia provocada por el virus COVID-19: el tecnoestrés docente. Para ello, se examinaron 139 documentos científicos indexados en la base de datos de Web of Science durante ese periodo, cuyo contenido se analizó a través de la hoja de cálculo Excel y el programa VOSviewer. Para garantizar la calidad del procedimiento metodológico, se utilizó el protocolo PRISMA. En primer lugar, se realizó un análisis bibliométrico de las publicaciones extraídas, tomando como referencia varios indicadores de producción y de dispersión. En segundo lugar, se realizó un análisis de redes, con objeto de intentar comprender la estructura de colaboraciones entre países y la estructura conceptual del tema objeto de estudio. Los resultados ponen de relieve que la información científica existente sobre el tecnoestrés en docentes es escasa, que se encuentra muy dispersa por áreas de investigación y que no existen grandes productores sobre la temática. Asimismo, el COVID-19 ha sido un punto de inflexión determinante que ha generado el mayor porcentaje de producción científica registrado hasta la fecha, lo cual está contribuyendo a dar mayor visibilidad al tecnoestrés como riesgo psicosocial laboral y a la profesión docente como uno de los colectivos más vulnerables.
Keywords: análisis bibliométrico; tecnoestrés; TIC; mapa de redes; docencia; COVID-19; bibliometric analysis; technostress; ICT; social network mapping; teaching